1993
DOI: 10.1073/pnas.90.15.7270
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane signaling in human polymorphonuclear neutrophils: 15(S)-hydroxy-(5Z,8Z,11Z,13E)-eicosatetraenoic acid modulates receptor agonist-triggered cell activation.

Abstract: ABSTRACT15(S)-Hydroxy-(5Z,8Z,11Z,13E)-eicosatetraenoic acid (15-HETE) exerted a time-and concentrationdependent inhibition of superoxide anion (O°) production and exocytosis of both azurophil and specific granule constituents from human polymorphonuclear neutrophils (PMN) stimulated with the receptor-specific agonists, N-formylmethionylleucylphenylalanine (FMLP), platelet-activating factor, and leukotriene B4, but not that elicited by phorbol 12-myristate 13-acetate. 15-HETE did not alter the binding of FMLP t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 39 publications
1
27
0
1
Order By: Relevance
“…In particular, 15-HPETE was a highly effective inhibitor of TNF production by macrophages stimulated with a variety of agonists. The findings signify another immunoregulatory mediator associated with inflammation and cell activation, and support and extend previous reports that showed that a product of the lipoxygenase pathway, namely 15-HETE, downregulates the inflammatory response by inhibiting neutrophil chemotaxis and the neutrophil oxygen radical production (14,15). Here our work emphasizes the ability of 15-HPETE to perform as a very effective inhibitor of TNF production.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In particular, 15-HPETE was a highly effective inhibitor of TNF production by macrophages stimulated with a variety of agonists. The findings signify another immunoregulatory mediator associated with inflammation and cell activation, and support and extend previous reports that showed that a product of the lipoxygenase pathway, namely 15-HETE, downregulates the inflammatory response by inhibiting neutrophil chemotaxis and the neutrophil oxygen radical production (14,15). Here our work emphasizes the ability of 15-HPETE to perform as a very effective inhibitor of TNF production.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, one major focus of pharmaceutical development has been the production of antiinflammatory agents, based on strategies to inhibit the generation of lipoxygenase products. Recently, the possibility that lipoxygenase-derived products can inhibit the inflammatory response has also been recognized, where 15(s)-hydroxy-5,8,11,13-eicosatetranoic acid (15-HETE) 1 was shown to cause inhibition of superoxide production and degranulation of neutrophils activated with f-met-leu-phe, platelet-activating factor, and LTB 4 (14), and to inhibit LTB 4 -induced neutrophil transmigration across endothelium (15). Such molecules, together with the possibility of making synthetic derivatives with desirable properties, can often be considered as avenues to develop appropriate antiinflammatory agents for potential use in inhibiting allergic and autoimmune inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism by which the DiHOMEs inhibit the respiratory burst is distinct from that of other respiratory burst inhibitors such as nitrolinoleate, cyclosporin H, lipoxin A4, or 15-HETE, which inhibit multiple aspects (both superoxide production and degranulation) of neutrophil activation (Coles et al 2002;Wenzel-Seifert et al 1991;Smith et al 1993;Gewirtz et al 1999;Hachicha et al 1999). The inhibitory effect of the methyl DiHOMEs is rapid, and does not require a preincubation step.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also indicate that tulathromycin drives the synthesis of LXA 4 , thereby lowering the total levels of 15(S)-HETE that are secreted and presented within the cell. Little is known about the actions of 15(S)-HETE itself; however, there is evidence to suggest that it exerts both anti-and proinflammatory actions (51)(52)(53). Phospholipase D has a variety of roles in inflammation and cell survival.…”
Section: Fig 3 Tulathromycin Reduces Levels Of Prostaglandin E 2 In Cmentioning
confidence: 99%